Tema Hukum Tata Negara: ANALISIS INDIKATOR NILAI PANCASILA SEBAGAI PEDOMAN META-YURIDIS DALAM PEMBENTUKAN KEBIJAKAN DAN PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Moh. Haris Lesmana; Adi Nur Rohman Rohman; Holly Muridi Zham-Zham (Jurnal Hukum Lex Generalis, 2025)
The Pancasila Value Indicators are a meta-legal guide introduced by BPIP to align the substance of policies and regulations with Pancasila values. However, its implementation faces fundamental issues impacting legal certainty, institutional governance, and consistency in law-making. This study aims to examine the application and formulate an ideal concept of the Pancasila Value Indicators, expected to realize law in accordance with Pancasila. The research findings show that BPIP's legitimacy, relying on a Presidential Regulation, limits the recognition and binding power of its normative products. Therefore, strengthening BPIP through legislation, explicit integration of indicators, and technical guidelines is essential.